Neighborhoods of last resort: how landlord strategies concentrate violent crime - Gomory, Henry (Criminology, 2023)
Studies of crime hot spots have argued that landlords’ management styles, specifically their tenant screening and property monitoring techniques, affect crime. These studies, however, have rarely considered the political-economic contexts in which these actions take place: specifically, how landlords’ behaviors are shaped by, and themselves reproduce, larger rental market structures. Drawing on data pertaining to eviction rates, criminal incidents, housing code violations, and landlord behavior in Milwaukee, Wisconsin, this study documents how extractive rental management strategies, such as weak tenant screening, frequent eviction filings, and property disinvestment, concentrate crime at particular properties. In turn, high rates of crime in a neighborhood incentivize these extractive landlord strategies. By showing how landlords’ economic strategies are central to urban crime geographies, this study contributes to our understanding of third-party policing by revealing the limits of market-based solutions to place management dilemmas.